ARM7 Educational board - Asrani, Lit (LAP LAMBERT Academic Publishing, 2013)
An embedded system is any computer system or computing device designed to perform a dedicated function. Industrial machines, automobiles, cameras, household appliances, vending machines as well as the more obvious cellular phone and Personal Digital Assistant (PDA) are among some of the embedded systems are usually equipped with inexpensive microprocessors and small memory footprint. The aim of this project was to produce an ARM7 processor based embedded system with various capabilities, at a small board size and a lower cost Thus, it’s suitable for educational purpose. This project involve the development process of an embedded board starting from circuit design, PCB layout and then the development of a simple testing application.